Metastable States of Multiscale Brain Networks Are Keys to Crack the Timing Problem - Gili, Tommaso; Ciullo, Valentina; Spalletta, Gianfranco (Frontiers in Computational Neuroscience, 2018)
The dynamic nature of the environment where we live in and the need to interact with it, predicting events in our context, provided strong evolutionary pressures for the brain functioning to process temporal information and generate timed responses. As a result of these pressures, the human brain is able to process temporal information and generate temporal patterns. Despite the clear importance of temporal processing to cognition, learning, communication and sensory, motor and emotional processing, even the most basic mechanisms of how animals discriminate simple intervals or generate timed responses are still under debate. The lesson we learned from the last decade of research in neuroscience is that functional and structural brain connectivity matter. Specifically, it has been accepted that the organization of the brain in interacting segregated networks enables its function. In this paper we delineate the route to a promising approach for investigating timing mechanisms. We illustrate how novel insight into timing mechanisms can come by investigating brain functioning as a multi-layer dynamical network whose clustered dynamics is bound to report the presence of metastable states. We anticipate that metastable dynamics underlie the real-time coordination necessary for the brain’s dynamic functioning associated with time perception. This new point of view will help further clarifying mechanisms of neuropsychiatric disorders.